Microfluidic mixing using PDMS-based microporous structures - Liu, Dongdong (2020)
We showed that efficient mixing of fluid flows at microscales can be achieved by a simple type of micromixers based on microporous structures. We used sugar particles as templates for fabricating the microporous structures. We quantitatively studied the relation between the mixing performance and the characteristics of the microporous structures, and showed that permeability is the key indicator of the mixing performance. By visualizing the flow inside the microstructures using confocal microscope, we also found that flow passage having repetitive and sudden contraction–expansion is the chief factor leading to mixing enhancement.